2003
DOI: 10.1177/1077558703254698
|View full text |Cite
|
Sign up to set email alerts
|

Is the Promise of Cancer-Screening Programs Being Compromised? Quality of Follow-Up Care after Abnormal Screening Results

Abstract: Cancer screening has increased dramatically in the United States, yet in some populations, particularly racial minorities or the poor, advanced disease at diagnosis remains high. One potential explanation is that follow-up of abnormal tests is suboptimal, and the benefits of screening are not being realized. The authors used a conceptual model of access to care and integrated constructs from models of provider and patient health behaviors to review published literature on follow-up care. Most studies reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
144
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(151 citation statements)
references
References 92 publications
4
144
0
3
Order By: Relevance
“…1 A systematic review of follow-up care after abnormal screening tests for cervical, breast, and colon cancer showed that < 75% of women received timely and appropriate follow-up care. 2 The proportion of women who were followed after abnormal Pap tests varies dramatically across studies, ranging from 7% to 73%. 2,3 Cervical cancer is preventable through early detection and removal of premalignant changes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 A systematic review of follow-up care after abnormal screening tests for cervical, breast, and colon cancer showed that < 75% of women received timely and appropriate follow-up care. 2 The proportion of women who were followed after abnormal Pap tests varies dramatically across studies, ranging from 7% to 73%. 2,3 Cervical cancer is preventable through early detection and removal of premalignant changes.…”
Section: Introductionmentioning
confidence: 99%
“…2 The proportion of women who were followed after abnormal Pap tests varies dramatically across studies, ranging from 7% to 73%. 2,3 Cervical cancer is preventable through early detection and removal of premalignant changes. There are few data to indicate what the optimal diagnostic and treatment intervals are that might ensure the best chances of survival from cervical cancer detected by screening.…”
Section: Introductionmentioning
confidence: 99%
“…16 In our study, ultrasound, cytology and physician consultation were provided on site for Kayole and South B sites, which explains the follow-up time of 1 day; however, availability of these services did not statistically influence return of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Non-navigated (n = 38) 23.7 (9) 76.3 (29) Navigation (n = 38) 57.9 (22) 42.1 (16) Overall, factors that were associated with return for followup included navigation (p = 0.003), marital status (p = 0.02) and education status above secondary school (p = 0.007). The rest of the factors were not significant (Table 4).…”
Section: Return Defaultermentioning
confidence: 99%
“…Previous studies showed less than 25% of these vulnerable women received adequate follow-up care after an abnormal cancer screening test. 8,9 In addition, the prevalence of depression is higher in vulnerable populations, [10][11][12][13][14][15][16] and twofold higher in women than men. National annual prevalence estimates for women range between 4 -14%.…”
mentioning
confidence: 99%